COVID-2019 : A BUDDHIST PROBLEM ANALYSIS TOOL FOR THAI SOCIETY - Pinitkit, Phra Jamrat Jotidhammo; Thepprawin Chanraeng, Thepprawin (Journal of Graduate MCU KhonKaen Campus, 2021)
The current Covid-21 epidemic crisis affects people around the world, regardless of their religion, nationality and national belief. As well as the increasingly severe impacts on living an unhappy life Until becoming a common problem of humanity Buddhists in Thai society are also affected by this problem. Nevertheless, it is still fortunate for Buddhists whose Lord Buddha has provided a vital tool for problem analysis and solutions for solving them completely. In addition, the tool is ready to be able to develop the potential of intelligence which is a protection against the plague that occurs, such as the first level tool, the look of the plague (suffering), the second tool, the quest for the origin of the epidemic (happiness), the tool. The third piece, Treatment and Prevention to deal with the Epidemic (Rage), and the 4th Tool, Creating a Troubleshooting Tool to Address the Epidemic (Makkah) Problems, which the relevant departments can use these tools to deal with. In all respects in Thai society